PENGARUH PEMBANGUNAN MANUSIA DI BIDANG KESEHATAN, PENDIDIKAN DAN DAYA BELI TERHADAP PERTUMBUHAN EKONOMI DI BLITAR RAYA TAHUN 2000 - 2014 - Herdianti, Widya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Indonesia is one country that has the largest population in the world. With the large number of the population, human development must be prioritized in order to improve the lives of people in the areas of health, education and purchasing power. But the existence of human development has created inequality, ecological damage and chained back human rights. Uneven development causes economic growth is not optimal in an area. Economic growth is not only supported by the government alone, but the community also had a role in it through human development in the areas of health, education and purchasing power. In the research described the effect of the health, education and the purchasing power has an effect on economic growth in Blitar in the year 2000-2014.Keywords: human development, health, education, purchasing power, economic growthÂ